Optimization of Diagnostics of Intrauterine Infection - Zarifovna, Omonova Guzal (Journal of Science in Medicine and Life, 2024)
Determination of diagnostic and prognostic criteria of intrauterine infection (IUI). Retrospective analysis of birth history of 302 patients and newborns; prospective study of 49 mother-newborn pairs at risk of IUI to develop a prognostic model and 53 pairs to evaluate the effectiveness of the developed algorithm. The diagnosis of IUI was confirmed/excluded based on the results of additional examination of the newborn on the first day after birth. Clinical and anamnestic criteria for the development of IUI were determined, taking into account their diagnostic information value, and a prognostic table was created for the risk of IUI development, which has an accuracy of 92%. The scheme of management of pregnant women at risk of IUI is offered according to the developed prognostic chart. In the case of IUI without a clear etiological factor, random prescribing of etiotropic drugs is not preferable compared to nonspecific therapy aimed at improving the functioning of the uteroplacental complex.